Data Transmission Method on a Room Condition Telemonitoring Application (IoT) - Mirdanies, Midriem (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2019)
Data transmission system in IoT applications such as telemonitoring, using cable or wireless, requires a robust data transmission method. In this paper, a room condition telemonitoring application has been made where all data are read from raspberry pi, and sent to a pc server every minute using LAN and Wifi media, then update to a webserver. The data are sent using the method proposed in this paper which using the UDP mechanism with several improvements. Experiments have been done using LAN and Wifi, and it is found that the data can be received perfectly, although there are interferences from communication media. The average processing time on a raspberry pi is 19 ms, while the average processing time on the pc server is 5 us. In addition, the average processing speed of the transmission data from raspberry pi to a pc server until ack is received by raspberry pi using LAN media is 0.04 second, while using Wifi media is 0.08 seconds. Based on the experiments, it was found that the proposed method was successfully implemented in the room condition telemonitoring.